2021
DOI: 10.1111/ocr.12510
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal and dental effects of Herbst appliance anchored with temporary anchorage devices: A systematic review with meta‐analysis

Abstract: Background The aim was to evaluate the efficiency of using temporary anchorage devices (TADs) in minimizing the anchorage loss and increasing the skeletal effects during correction of Class II malocclusion with Herbst appliance. Materials and methods Search without restrictions was performed up to January 2021 in three electronic databases (CENTRAL, MEDLINE and EMBASE) for randomized controlled trials (RCTs), prospective and retrospective cohort studies. The included studies assessed the dental and skeletal ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
1
5
0
2
Order By: Relevance
“…Comparing these results with those of the meta-analysis conducted by Yang ( 29 ) on the effects of the Herbst appliance on the sagittal position of the mandibular base (Pg_OLp), a greater Pog advancement was observed in the present study [3.34 mm ± 2.34 mm (Group 1) and 4.34 mm ± 2.41 mm (Group 2)] vs. the average of 1.45 mm found by the author. This confirmed the conclusions of Al-Dboush ( 30 ), stating that the combination of the Herbst appliance with TADs might increase the effectiveness of the traditional orthopedic treatment, thereby leading to a better projection of the chin, regardless of the growth pattern. On one hand, this outcome could be explained by greater control in the sagittal position of the lower incisors with skeletal anchorage, preserving the overjet needed for mandibular advancement ( 31 ).…”
Section: Discussionsupporting
confidence: 88%
“…Comparing these results with those of the meta-analysis conducted by Yang ( 29 ) on the effects of the Herbst appliance on the sagittal position of the mandibular base (Pg_OLp), a greater Pog advancement was observed in the present study [3.34 mm ± 2.34 mm (Group 1) and 4.34 mm ± 2.41 mm (Group 2)] vs. the average of 1.45 mm found by the author. This confirmed the conclusions of Al-Dboush ( 30 ), stating that the combination of the Herbst appliance with TADs might increase the effectiveness of the traditional orthopedic treatment, thereby leading to a better projection of the chin, regardless of the growth pattern. On one hand, this outcome could be explained by greater control in the sagittal position of the lower incisors with skeletal anchorage, preserving the overjet needed for mandibular advancement ( 31 ).…”
Section: Discussionsupporting
confidence: 88%
“…In particular, the effect of anchorage reinforcement on reducing lower incisor inclination (1i-ML; in degrees) will be assessed. The studies identified from two recently published systematic reviews (Al-Dboush et al, 2021;Huang et al, 2021) are pooled here and their data re-analysed. Some studies initially included in the original systematic reviews are excluded however, since they measured inclination of the lower incisors relative to the NB line and not to the mandibular line or did not report complete descriptive statistics pre-treatment, post-treatment, and in terms of treatment-induced changes (post minus pre).…”
Section: Theoretical Scenariomentioning
confidence: 99%
“…The effect of functional appliances depends on the degree of cooperation and compliance [ 16 , 17 ]. Therefore, removable functional appliances could only obtain dentoalveolar correction of Class II malocclusion without clinically significant skeletal changes [ 18 ]. Judged by these circumstances, the efficacy of functional appliances may not consistently manifest in routine clinical applications [ 19 ], which demands a more efficient, dependable, and secure therapeutic approach to stimulate mandibular growth.…”
Section: Introductionmentioning
confidence: 99%